Characterization of heavy metal contaminated soils in Northern Cyprus - (:unkn) unknown (SPRINGER, 2002)
The Lefke region of Northern Cyprus was a site of intense copper mining and smelting activities until the 1970s, which produced large tailings This study was initiated to characterize the heavy metal contamination of soils of the area and to assess the influence of this site on the surface seawater quality along the coastline. Soil and seawater samples were collected and analysed. Copper and arsenic concentrations exceeded the limits for 'extremely polluted' soils for some samples, which can be classified as 'polluted' by zinc, cadmium and lead. The results showed that seawater was seriously polluted by chromium, nickel and copper in the vicinity of the smelting facility. Copper and iron concentrations increased tenfold after rainfall (wet period); indicating the contribution of tailings to marine pollution. There is an urgent need for remediation treatment for the site.
Keywords: copper mining; Cyprus; heavy metals; sea pollution; soil pollution; MINING ACTIVITIES; REMEDIATION